Synthesis of Polyhedral Magnetite Particles by Hydrothermal Process under High Pressure Condition - Machmudah, Siti; Wahyudiono, Wahyudiono; Kanda, Hideki; Goto, Motonobu (ITB Journal Publisher, LPPM ITB, 2016)
Magnetite particles were successfully generated by hydrothermal synthesis using water at subcritical conditions. By changing the temperature and pressure at subcritical water conditions, the thermodynamics and transport properties of the water can be controlled, thus enabling to manage the way of crystal formation, morphology, and particle size. In this work, the experiments were carried out at temperatures of 250 Â°C and 290 Â°C and a pressure of 10 MPa with a reactor made of SUS 316 in a batch system. The synthesized particles were dried in vacuum condition and characterized by SEM and XRD. The XRD patterns showed that magnetite particles were dominantly formed in the particle products with a black color. The results showed that the magnetite particles formed had diameters of around 60 nm in all experiments with irregular polyhedral shaped morphologies.